End-of-Life Discussions From the Perspective of Social Care and Healthcare Professionals in Palliative Care - Kuusisto Anne; Saranto Kaija; Korhonen Päivi; Haavisto Elina (United States, 2026)
This study describes the state of end-of-life discussions in Finland. A qualitative descriptive study with thematic interviews was conducted. Data were gathered from palliative care unit nurses, physicians and social workers. Inductive content analysis was used. According to interviewees (n = 33), the state of end-of-life discussion included three main categories. First, optimal end-of-life discussion time included early end-of-life discussion, end-of-life discussion at different phases of severe illness, and flexibility and challenges in scheduling end-of-life discussion. Second, end-of-life discussion initiators included both healthcare professionals and non-healthcare professionals. Third, social care and healthcare professionals' experiences of end-of-life discussion consisted of the importance and challenge of end-of-life discussion, end-of-life communication skills development in multiprofessional care context, and end-of-life communication in multi-cultural care context. The results can be used to justify the need of a national strategy and systematic implementation on Advance Care Planning (ACP), considering the multiprofessional, multicultural and internationalizing operating environment.